Motivation of Students Choose The Faculty of Education and Science of Education University of Riau - Umari, Tri; Rosmawati, Rosmawati; Donal, Donal (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this research is to know the motivation of students to choose Faculty of Teacher Training and Education University of Riau which in the end will become university reference to create competitive advantage and to know and analyze student motivation to choose Faculty of Teacher Training and Education University of Riau.This research was descriptive quantitative.Where previously taken Sample using random sampling method. In this research will be seen the dominant encouragement of students choose Faculty of Teacher Training and Education University of Riau. From this research, it is known that students motivation in choosing Faculty of Teacher Training and Education of Universitas Riau is self drive 56,37%, because according to Talent and Interest owned by 19,59%, Parents encouragement equal to 11,46%, easy transportation Or close to 0,24%, since the cost of Lecture (financial ability) of 2.39%, and the Enviroment Enough (Master, Alumni and Friends) amounted to 9.24%.